Numerical evaluation of renovation packages for an existing multi-family building - Tanase Andra; Bejan Andrei – Stelian; Calota Razvan; Ene Alexandra (E3S Web of Conferences)
The energy efficiency of building and building systems is one of the main focus of the European countries determined to lower their impact on CO2 emissions with ambitions certain targets until 2030 and 2025. This includes the implementation of nearly zero-energy building (nZEB) standards and the widespread adoption of renewable energy sources. This paper aims to study the implementation of different strategies and renovation packages on an existing building in Bucharest, Romania, thus reducing primary energy consumption with up to 56% and CO2 specific emissions with up to 73%.